Curriculum Adaptation Model: Modifying the Mathematics Curricula for a More Inclusive Public School Deaf and Hard-of-Hearing Mainstream Classroom - De Jesus, Vitus Paul L. (Archīum Ateneo, 2024)
Few public schools in the Philippines offer basic education to the Deaf and Hard-of-Hearing (D/HH) learners in a mainstream classroom set up. The general education curriculum (GEC) of the Department of Education's (DepEd) K-12 Basic Education Program serves as the primary material for instruction guide. Studies, however, have expressed the need for modifications in the learning environment, curriculum, instruction and activities of language-challenged learners, especially those mainstreamed or placed in predominantly hearing classrooms. D/HH learners lagging behind their hearing counterparts in Mathematics performance and skills (e.g. additive/multiplicative reasoning, estimation, understanding of real numbers) has well been documented. In light of this well-established existence of D/HH learners' achievement gap in mathematics, and the benefits of curriculum modification, the study aims to conceptualize a curriculum adaptation model that informs the modification of any curriculum in mathematics into a form that is more appropriate and more responsive to both the hearing and D/HH learners, in a public school mainstream set up. The development process made use of the scientific and humanistic evaluation models of Tyler (1949) and Eisner (1994) to uncover the interaction of five curricular components of learner outcomes/competencies, time allocation, learning experiences, assessment of learning, and learning materials. How these curricular components work, act and interact with each other inform the creation of a mathematics curriculum adaptation model that benefits the D/HH learning community.